Short- and long-term influences of heavy metals on anionic drug efflux from renal proximal tubule - Terlouw, Sylvie Annette; Graeff, Claudia; Fricker, Gert (The journal of pharmacology and experimental therapeutics, 2002)
We recently demonstrated in isolated killifish renal proximal tubules that two classes of nephrotoxicants, aminoglycoside antibiotics and radiocontrast agents, rapidly decrease transport mediated by multidrug resistance protein 2 (Mrp2) by causing endothelin (ET) release and signaling through an ETB receptor and protein kinase C (PKC) (Masereeuw et al., 2000; Terlouw et al., 2001). In the present study, we used killifish proximal tubules, fluorescein methotrexate, a fluorescent model substrate for Mrp2, and confocal microscopy to examine the effects of two heavy metal salts (CdCl2 and HgCl2) on Mrp2 function. Three patterns of effects were seen. First, exposing tubules to 10 μM CdCl2 or 100 nM HgCl2 for 30 min reduced Mrp2-mediated transport. This reduction was abolished by the ETB receptor antagonist, RES-701-1, and by the PKC-selective inhibitor, bis-indolylmaleimide I; neither of these pharmacological tools by itself affected transport. As with aminoglycoside antibiotics and radiocontrast agents, the acute effects of 10 μM CdCl2 or 100 nM HgCl2 on transport were also blocked by nifedipine, suggesting that Ca2+ also initiated cadmium and mercury action. Second, exposure to higher concentrations of CdCl2 and HgCl2 appeared to be toxic. Third, exposing tubules for 6 to 24 h to lower levels of CdCl2 increased Mrp2-mediated transport and Mrp2 immunostaining at the luminal membrane of the proximal tubule cells. Together, these findings indicate that exposure of renal proximal tubules to heavy metals initially leads to reduced Mrp2 function but is followed by an induction in Mrp2-mediated transport after long-term exposure.
Gesehen am 25.04.2017